Characterization of Nutritional Composition, Antioxidative Capacity, and Sensory Attributes of Seomae Mugwort, a Native Korean Variety of Artemisia argyi H. Lév. & Vaniot. (13th October 2015) - Kim, Jae Kyeom; Shin, Eui-Cheol; Lim, Ho-Jeong; Choi, Soo Jung; Kim, Cho Rong; Suh, Soo Hwan; Kim, Chang-Ju; Park, Gwi Gun; Park, Cheung-Seog; Kim, Hye Kyung; Choi, Jong Hun; Song, Sang-Wook; et al.
Abstract : Few studies have investigated Seomae mugwort (a Korean native mugwort variety of Artemisia argyi H. Lév. & Vaniot), exclusively cultivated in the southern Korean peninsula, and the possibility of its use as a food resource. In the present study, we compared the nutritional and chemical properties as well as sensory attributes of Seomae mugwort and the commonly consumed species Artemisia princeps Pamp. In comparison with A. princeps, Seomae mugwort had higher contents of polyunsaturated fatty acids, total phenolic compounds, vitamin C, and essential amino acids. In addition, Seomae mugwort had better radical scavenging activity and more diverse volatile compounds than A. princeps as well as favorable sensory attributes when consumed as tea. Given that scant information is available regarding the Seomae mugwort and its biological, chemical, and sensory characteristics, the results herein may provide important characterization data for further industrial and research applications of this mugwort variety.